(untitled) (Journal of Geography and Environmental Management, 2017)
This article examines the complex formation and development of the historical and geographical place names Saryarka bases. The features of the location and the etymology of mountain systems on the territory of Saryarka such as Kokshetau, Yereimentau, Bayanaul, Chingiztau, Kyzylaray, Karkaraly, Ulytau.Also, given the mention of geological and geomorphological structure of the mountain ranges of Saryarka, focusing on tourism development in the region. Toponymic investigation is very difficult, mostly it required geography, history, linguistics and sometimes archaeological knowledge. Mostly toponyms identified as characteristic signs of local geological structure, mountains rocks composition, mineral resources and other things. Applied issues of toponymy take an important part in kazakh geographical names research which is closed to geology. Description of mineral resources’ local toponymies have historical-archeological and geological basis. Also mineral resources toponymic system adds important characteristics to geographical names and provide geologists with required information to explore mineral resources.At the same time, the etymology of oronyms Saryarka determined historical and geographical, linguistical approaches, and dealt with in accordance with the laws of propagation of names.